2010
DOI: 10.2147/ijwh.s11887
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia in women with asymptomatic malaria parasitemia at first antenatal care visit at the University of Calabar Teaching Hospital, Calabar, Nigeria

Abstract: Background:Anemia in pregnancy in malaria endemic areas is a public health challenge that has contributed either directly or indirectly to maternal morbidity and mortality in our environment. Anemia and malaria during pregnancy are highly preventable and treatable.Objective:The aim of this study is to assess the prevalence of anemia in asymptomatic malaria parasitemic women at first antenatal visit in a tertiary hospital facility.Method:The study was conducted at the antenatal clinic of the University of Calab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
49
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 7 publications
10
49
9
Order By: Relevance
“…The overall prevalence of anemia in this study is lower than reported figures of 46.2% and 69.1% from Benin City, Nigeria and Kisumu, Western Kenya [38,39] . However, the prevalence of anemia among women with malaria parasitaemia is more or less comparable to 59.6% reported from similar study group in Calabar, Nigeria [41] .Anemia was three times higher among those with malaria parasitaemia compared to those without malaria parasitaemia in this study. This direct correlation between severity of parasitaemia and anemia was noted by other researchers elsewhere [15,27,32,38,40,41] .This higher prevalence rate of anemia among women with malaria parasitaemia is attributed to increased haemolysis of parasitized red blood cells by the reticuloendothelial system in the body [4,42,43] .…”
Section: Discussionsupporting
confidence: 75%
“…The overall prevalence of anemia in this study is lower than reported figures of 46.2% and 69.1% from Benin City, Nigeria and Kisumu, Western Kenya [38,39] . However, the prevalence of anemia among women with malaria parasitaemia is more or less comparable to 59.6% reported from similar study group in Calabar, Nigeria [41] .Anemia was three times higher among those with malaria parasitaemia compared to those without malaria parasitaemia in this study. This direct correlation between severity of parasitaemia and anemia was noted by other researchers elsewhere [15,27,32,38,40,41] .This higher prevalence rate of anemia among women with malaria parasitaemia is attributed to increased haemolysis of parasitized red blood cells by the reticuloendothelial system in the body [4,42,43] .…”
Section: Discussionsupporting
confidence: 75%
“…The prevalence of anaemia at first antenatal visit in this study was lower than 94.07% reported by Nduka et al [11]. It did not differ from 60.8% reported by Okafor et al [12]; 59.6% reported by Agan et al [13], 62.4% reported by Ogbodo et al [14] and 66% reported by Erhabor et al [15] (Tables 1 and 2). Furthermore, it was higher than 30% reported by Douamba et al [16] and 20.3% reported by Buseri et al [17].…”
Section: Resultscontrasting
confidence: 58%
“…[6][7][8][9][10][11][12][13] In Benin and Abakaliki the prevalence was 20% and 16% as reported by Okpere et al and Uneke et al respectively, in their research among booked antenatal women. [6,13] [7,8,11,12] The prevalence of 77.6% in this study correlated with the findings among the unbooked pregnant women as shown above, even though it is lower than that in findings in Ibadan southwest Nigeria and Calabar south-south Nigeria and higher than that in findings in Enugu southeast Nigeria and Kano northern Nigeria. The large variation in the reported prevalence of malaria parasitemia may be multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Up to 16-95.4% of asymptomatic parasitemia in pregnancy had been reported in various studies with associated maternal anemia and low birth weight. [6][7][8][9][10][11][12][13] This study was aimed at determining the prevalence of asymptomatic malaria parasitemia among unbooked clients presenting in labor in the Federal Teaching Hospital Abakaliki. This will help to detect those who have the problem and appropriate treatment administered in the short run and to show the enormity of the problem to help create awareness and to scale up preventive measures against this public health problem in the long run.…”
Section: Introductionmentioning
confidence: 99%